Fabrication and Characterization of Hybrid Solar Cells Based on Perovskite Materials. (10th September 2015) - Abdel-Fattah, Tarek M; Ebrahim, Shaker; Soliman, M; Anas, M; Moustafa, E
Abstract : The aim of this study is to prepare and characterize the perovskite as hole transferring and electron transferring materials to be used in the fabrication of solar cells. Inverted perovskite solar cells have been fabricated with the following design: fluorine tin oxide (FTO)/electron injection layer (EIL)/active layer/hole injection layer (HIL)/metallic upper electrode. CuI as hole injection material matched the energy levels with FTO. ZnO nanoparticles was prepared by sol gel method and used as electron injection layer. Aging the ZnO sol for one month yields a better cell performance due to the formation of nanoridges structure. The achievable perovskite solar cell efficiency, fill factor, open circuit voltage and short circuit current density were found to be 2.4%, 0.67, 1.0 V and 0.037 mA/cm 2, respectively for the following device structure: FTO/ZnO/CH3 NH2 PbI3 /CuI/Au.